If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5p + -10 = 2(2p + -15) + p Reorder the terms: -10 + -5p = 2(2p + -15) + p Reorder the terms: -10 + -5p = 2(-15 + 2p) + p -10 + -5p = (-15 * 2 + 2p * 2) + p -10 + -5p = (-30 + 4p) + p Combine like terms: 4p + p = 5p -10 + -5p = -30 + 5p Solving -10 + -5p = -30 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. -10 + -5p + -5p = -30 + 5p + -5p Combine like terms: -5p + -5p = -10p -10 + -10p = -30 + 5p + -5p Combine like terms: 5p + -5p = 0 -10 + -10p = -30 + 0 -10 + -10p = -30 Add '10' to each side of the equation. -10 + 10 + -10p = -30 + 10 Combine like terms: -10 + 10 = 0 0 + -10p = -30 + 10 -10p = -30 + 10 Combine like terms: -30 + 10 = -20 -10p = -20 Divide each side by '-10'. p = 2 Simplifying p = 2
| 1/5b=1/5b-14 | | 1/3(b+6)=1/4b+8 | | 4y-18=-13+5y | | n/3=15 | | 0=(2x-1)(-x+-1) | | 1/3x+6=12 | | (3(x-5))/2=(2(x+5))/3 | | 3(2x+4)=2(X-2)+4x | | 4(3+2x)=20 | | 2t-22=-28+t | | -6-4/3h=-2/3h | | -4=x/9 | | y-1=1.6(x-4) | | -c-12+3c=2(c-6) | | 4(n-5)=n-2 | | 5y+2(y-7)=3(y+1)-2 | | 7x+70=2x+120 | | 3-1/5x=4 | | 7x+55=2x+115 | | -2(-1)-6y=-10 | | y-1=5/3(x-4) | | 24/10 | | x/5+3=6 | | -1/6-2/5 | | 18-6e=3(9+2e) | | 10x-24=-8x+2 | | 182-7x=29x-18 | | 14093.89=2*3.14*r^2+2*3.14*r*98.4 | | y-15=8(x-0) | | 9r+4=6r-5 | | 3(y)-7=8 | | x/12-7=8 |